Books that changed history From the Art of War to Anne Frank's diary - Collins, Michael 1960-; Black, Alexandra; Cussans, Thomas; Farndon, John 1960-; Parker, Philip 1965- (Dorling Kindersley Ltd., 2017)
Turn the pages of the most famous books of all time and marvel at the stories behind them. Over 75 of the world's most celebrated, rare, and seminal books are examined and explained in this stunning treasury. 'Books That Changed History' is a unique encyclopedia spanning the history of the written word, from 3000 BCE to the modern day. Chronological chapters show the evolution of human knowledge and the changing ways in which books are made. Discover incredible coverage of history's most influential books including the Mahabharata, Shakespeare's First Folio, The Diary of Anne Frank, and Penguin's first ever paperbacks. From Darwin's groundbreaking On the Origin of Species to Louis Braille's conception of the Braille system that we still use today, these are world famous books that have had the biggest impact on history. Every book is presented with breathtaking photography and fascinating biographies of those who created them. 'Books That Changed History' gathers dictionaries, diaries, plays, poems, treaties, and religious texts into one stunning celebration of the undisputed power of books
Includes index
Keywords: Books and reading; Influence (Literary, artistic, etc.); History